Review of the subgenus Ceratopius Clément, 1927 of the genus Metopius Panzer (Hymenoptera: Ichneumonidae: Metopiinae) from Japan - Morishita, Shunsuke; Watanabe, Kyohei (Zootaxa, 2026)
Japanese species of the subgenus Ceratopius Clément of the genus Metopius Panzer are reviewed. Ten species are recognized in the Japanese fauna. The following five new species are described: M. (C.) flavofacies sp. nov.; M. (C.) iris sp. nov.; M. (C.) minimus sp. nov.; M. (C.) splendens sp. nov.; M. (C.) violaceus sp. nov. Taxonomic status of M. (C.) dissectorius pieli Uchida, 1940 is changed from a subspecies of M. (C.) citratus (Geoffroy, 1785) to a separate species. Metopius (C.) pieli is newly recorded from Japan. Metopius (C.) baibarensis Uchida, 1930, M. (C.) carinatus Tolkanitz, 1985, M. (C.) dissectorius imperfectus Uchida, 1930, M. (C.) dissectorius taiwanensis Chiu, 1962, M. (C.) dissectorius trifasciatus Uchida, 1930, and M. (C.) elegans Tolkanitz, 1985 are newly synonymised under M. (C.) fuscipennis. A key to Japanese species of this subgenus is provided.